Co-infection with dengue, zika, chikungunya in a six-year-old patient in Bamako, Mali - Cissoko, Yacouba; Akakpo, Essenam AA; Koné, Amadou; Doumbia, Yama; Doucouré, Sékou I; Soumaré, Mariam; Diarra, Bassirou; Konaté, Issa; Doumbia, Seydou; Dao, Sounkalo (The Journal of Infection in Developing Countries, 2026)
Introduction: The burden of arboviral infections remains underestimated in sub-Saharan Africa due to the similarity of symptoms with malaria and other tropical febrile illnesses. Simultaneous infection with three arboviruses sharing the same vector is rarely reported. Case presentation: We report here the case of a six-year-old girl diagnosed by multiplex real time-polymerase chain reaction for infection involving dengue, zika and chikungunya viruses with no severe symptoms and good clinical improvement with symptomatic treatment in Bamako, Mali. Conclusions: Co-circulation of different arboviruses is possible in urban context where Aedes mosquito vectors are emerging. Further studies are needed to explore the epidemiology and the clinical features of these coinfections.